DAMPAK KEBIJAKAN TAX HOLIDAY PADA ALIRAN MASUK FDI INDUSTRI PIONIR DI INDONESIA - Muhammad Tri Karimullah (Bina Ekonomi, 2018)
ABSTRACTIn 2011, the Indonesian government issued a Tax Holiday policy as an incentive to attract investment. However, the policy is still considered not optimal in increasing FDI realization in Indonesian pioneer industry. This study aims to analyze the influence of the Tax Holiday policy in increasing the realization of direct investment in Indonesian pioneer industry; as well as to investigate other factors influencing the inflow of Foreign Direct Investment (FDI) in the industry. The results of descriptive analysis and VECM show that Tax Holiday policy has increased the realization of direct investment of pioneer industries in 2012 and 2014 by 5.17% and 4.66%, respectively. In addition, there are other factors that influence the FDI inflow to the Indonesian pioneer industry, namely: GDP, economic openness, labor force participation, loan interest rates, exchange rates, and per-capita GDP. Maintaining the stability of these factors is important to support Tax Holiday's policy in increasing direct investment activities in Indonesia pioneer industry.Keywords: tax holiday; Foreign Direct Investment; Indonesian pioneer industry